Psychological environmental characteristic: Coaching capabilities support the development of grassroots football players in Indonesia and Malaysia - Zulakbal Abd Karim, Jaffry Zakaria (Tanjung Malim, 2024)
Psychological environmental characteristic: Coaching capabilities support the development of grassroots football players in Indonesia and Malaysia by Zulakbal Abd Karim, Jaffry Zakaria